2008
DOI: 10.1016/j.jhevol.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A critique of the chronometric evidence for hominid fossils: I. Africa and the Near East 500–50ka

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 132 publications
1
48
0
Order By: Relevance
“…In the Middle East, blades are found in the Amudian industry of the Late Lower Paleolithic. The dating of this industry is the subject of debate based on discordant ESR ages (on teeth) which place this industry in OIS 7 (186-245 kyr), as opposed to TL ages (on burnt flint) which place the Amudian in OIS 9 (Porat et al, 2002;Barkai et al, 2005;Millard, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Middle East, blades are found in the Amudian industry of the Late Lower Paleolithic. The dating of this industry is the subject of debate based on discordant ESR ages (on teeth) which place this industry in OIS 7 (186-245 kyr), as opposed to TL ages (on burnt flint) which place the Amudian in OIS 9 (Porat et al, 2002;Barkai et al, 2005;Millard, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of dated fossil hominins from southern Africa coeval with the KP-1 Fauresmith, this assemblage remains bracketed by the Saldanha (Elandsfontein) skull, attributed to Homo heidelbergensis or archaic Homo sapiens (Klein et al, 2007;Rightmire, 2001), associated with Acheulean artifacts and dated by faunal associations to ca. 320-790 kyr (Millard, 2008) [or 600-1,000 kyr (Klein et al 2007)], and the Florisbad skull associated with MSA artifacts, usually attributed to early archaic Homo sapiens and directly dated by ESR to 259 AE35 kyr (Grü n et al, 1996;Rightmire, 2001). The KP-1 ages clearly demonstrate that the advent of blade production predated the appearance of modern Homo sapiens in Africa, as attested to by the Kibish Formation fossils with an inferred age of 195 AE 10 ka and the Herto H. sapiens dating to 160 AE 4-154 AE 14 ka (Millard, 2008 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we have to work with what is available, and I will now briefly discuss the most complete or significant specimens discovered so far, region by region (figure 1). Wider and more detailed compilations on the material and its dating can be found in Schwartz & Tattersall [32], Millard [33], Klein [34] and Wood [35].…”
Section: The African Middle-early Late Pleistocene Fossil Record Of Hmentioning
confidence: 99%
“…Notwithstanding Millard's statement, other workers have taken his statement to mean that the age of Omo I and Omo II is not known better than these limits (e.g., Endicott et al, 2009;Cartmill and Smith, 2009), reinforced by Fig. 4 in Millard (2008). Other lines of evidence presented previously have been ignored.…”
Section: Introductionmentioning
confidence: 96%
“…It was also suggested that the lower part of Member II was most likely deposited at w172 ka, providing a narrower bracket for the age of the fossils. Millard (2008) reevaluated the laser fusion ages on these units, and concluded that the limits that can be placed on the hominin remains are "189.6 AE 1.4 ka (sample 02-01B) and 99.8 AE 1.0 ka (sample 99-274A), but actually lie much closer in time to the former" [Emphasis ours]. Notwithstanding Millard's statement, other workers have taken his statement to mean that the age of Omo I and Omo II is not known better than these limits (e.g., Endicott et al, 2009;Cartmill and Smith, 2009), reinforced by Fig.…”
Section: Introductionmentioning
confidence: 99%